STUDENTS’ PERCEPTION ON THE USE OF VLOG MEDIA IN SPEAKING SKILL - Salsabillah Abdullah (JELLi Journal, 2021)
This research is descriptive qualitative research. The objectives of the research is to know what are students’ perception on the use of vlog media. The subject of the research is tenth grade students of Putra Pelita Vocational High School, located at Cibitung Tengah-Tenjolaya. There were eight participants of students in this research. The data collecting technique used by the writer are interview and self[1]reflection. The writer did interview by audio recording on Whatsapp application and self-reflection by direct writing on the paper. First : The result showed that participants felt easier when learning speaking skill using vlog media. They argued that vlog as learning media to improve their speaking skill. Then, when practice using vlog media they can increase confidence, increase a vocabulary and also makes it easier for students to talk and be able to express ourselves. Second : the result of the interview and self-reflection showed that the result is positive. Participants agreed that using vlog media can help them in learning speaking skill. Furthermore, this media can be an alternative way for teacher to teach speaking. Thus it can be concluded that learning speaking skill using vlog media has proven to be effective in increasing students’ speaking skill